Short-term Analysis of the Residual Volume of an Eye Drop Following 23-Gauge Microincision Vitrectomy Surgery - Kang, Yong Koo; Im, Jong Chan; Shin, Jae Pil; Kim, In Taek; Park, Dong Ho (Korean journal of ophthalmology, 2017)
To evaluate the change of residual volume of eye drop after instillation in patients with 23-gauge microincision vitrectomy surgery (MIVS). Patient who were treated 23-gauge MIVS from November 2014 to July 2015 were included. The residual volume was defined as the amount of remnant eye drop in patient's eyes after instillation, calculated as the difference between instillation volume and spilled volume of eye drop. Calculation of residual volume of eye drop was performed one day before surgery, and daily from postoperative day 1 to day 5. Forty consecutive patients were included. The residual volume of eye drop decreased from 30.3 ± 1.4 μL at baseline to 13.0 ± 1.5 μL at day 1, 18.3 ± 1.6 μL at day 2, 24.7 ± 1.5 μL at day 3, and 27.9 ± 1.4 μL in day 4, postoperatively (p < 0.001, respectively). The volume at postoperative day 5 was 29.4 ± 1.3 μL, but it was not different from the volume at baseline (p = 0.105). The change of residual volume was significantly correlated with postoperative chemosis (r = 0.672, p < 0.001) and effected by the number of quadrant with postoperative chemosis (p < 0.05). This study shows that postoperative residual volume of eye drop after instillation decreased until postoperative day 4, and postoperative chemosis affects the change of residual volume. Thus, checking proper use of eye drops and teaching about instillation technique by physician is necessary for patients with 23-gauge MIVS.